Advances in Crop Improvement and Delivery Research for Nutritional Quality and Health Benefits of Groundnut (Arachis hypogaea L.) - Ojiewo, Chris O.; Janila, Pasupuleti; Bhatnagar-Mathur, Pooja; Pandey, Manish K.; Desmae, Haile; Okori, Patrick; Mwololo, James; Ajeigbe, Hakeem; Njuguna-Mungai, Esther; Muricho, Geoffrey; Akpo, Essegbemon; Gichohi-Wainaina, Wanjiku N.; et al. (Frontiers in Plant Science, 2020)
Groundnut is an important global food and oil crop, contributing to household food, nutrition and income security. Its consumption, processing and international trade is however, constrained by a number of genetic and biotic factors related to the grain nutrient profile. These include Aflatoxin, which is a prominent food safety challenge, allergens and oil profile, especially oleic/linoleic acid balance. This review paper highlights technological advances in crop improvement research to improve groundnut nutrient profile for better food, nutrition, health, and economic outcomes. Significant advances have been made in setting stage for marker-assisted allele pyramiding for different aflatoxin resistance mechanisms - in vitro seed colonization, pre-harvest aflatoxin contamination and aflatoxin production - which, together with pre- and post-harvest management practices, will go a long way in mitigating the Aflatoxin menace. A breakthrough in aflatoxin control is in sight with overexpression of antifungal plant defensins, and through host-induced gene silencing in the aflatoxin biosynthetic pathway. Similarly, genomic and biochemical approaches to allergen control are in good progress, with the identification of homologs of the allergen encoding genes and development of monoclonal antibody based ELISA protocol to screen for and quantify major allergens. Double mutation of the allotetraploid homeologous genes, FAD2A and FAD2B, has shown potential for achieving >75% oleic acid as demonstrated among introgression lines. Significant advances have been made in seed systems research to bridge the gap between trait discovery, deployment and delivery through innovative partnerships and action learning.